Praktik Pembelajaran Karakter Melalui Literasi Baca di Sekolah - Restoe Ningroem; Aster Pujaning Ati; Mu’thia Mubasyira; Nana Suyana (Jurnal Ilmiah Wahana Pendidikan, 2022)
Character learning is very important in the formation of national buildings. This education is an education whose results cannot be directly felt by parents and educators. In addition, this education requires a long time. With the reading strategy, it is hoped that the student's character can be embedded and well patterned. Through good and appropriate reading, students are able to absorb all what they have read. The purpose of this research is to reveal how to cultivate students' character by practicing reading, and what students and teachers face at school. This research uses qualitative methods and literature study research. Respondents were 4 teachers and 4 junior high school students. The results of the study stated that the teacher inserted character material in the middle of the subject, besides that the teacher gave directions to students to read in the library or elsewhere. Constraints faced by students in realizing reading literacy, incomplete reading sources and real examples from teachers and parents at home